MORPHOLOGICAL CHARACTERISTICS OF THE HERMANN’S TORTOISE (TESTUDO HERMANNI GMELIN, 1789) IN THE SOUTH-EASTERN PART OF KOSOVO AND METOHIJA - Labus, Nenad; Savić, Aleksandra; Živić, Nebojša; Babović-Jakšić, Tatjana (Bulletin of Natural Sciences Research, 2016)
In this paper we present the results of the analysis of  morphological characteristics of the Hermann’s tortoise from three localities in south-eastern part of Kosovo and Metohija. 75 adult Hermann's tortoises (33 males and 42 females) have been analyzed. Morphometric analisys has been done on 7 traits. We considered the plastron black pigmentation patterns and frequencies for each pigmentation states were calculated. Females were larger than males for all morphometric traits. Based on the most important dimensions of carapace and plastron length and width, the Hermann's tortoises from the south-eastern part of Kosovo and Metohija are the most similar to the individuals of the population from the southern part of the Balkan Peninsula (the southern part of Serbia and the northern part of Greece). In relation to the populations from central and eastern Serbia, individuals from our studed area have higher values.
Keywords: Kosovo and Metohija; Hermann’s tortoise; morphometry